Evaluation of the effects of seed treatment with GA3 and pre-chilling on seed germination characteristics of Salvia species - Maryam Palizdar; Reza Tavakkol Afshari; Ziba Jamzad; Mohammadreza Ardakani; Parisa Nejat Khah (علوم و فناوری بذر ایران, 2021)
This research was carried out to evaluate the germination response of eleven Salvia species to application of Gibberellic acid (GA3) and pre-chilling treatments in the Iran Research Institute of Forests and Rangelands during 2012. Germination responses of the seeds were investigated under control treatment, 2-levels of Gibberellic acid (GA3) treatments with 500 mg/L (for 24 and 48 hours) and 2-levels of pre-chilling treatments at 4°C (for 2 and 4 weeks). The germination percentage and rate, as the physiological traits of the species, were studied based on a completely randomized design with four replications. Based on the results, applying the Gibberellic acid (GA3) treatment for 24 hours increased both the germination percentages and rates as compared to control; but the treatment for 48 hours was insignificantly changed the two mentioned parameters comparing to control. On the other hand, the pre-chilling treatment of seeds for 2 weeks also caused a significant increase in the above parameters as compared to the control treatment; while they were insignificantly different from the control treatment by the use of pre-chilling treatment for 4 weeks.